Blocking the CD39/CD73 pathway synergizes with anti-CD20 bispecific antibody in nodal B-cell lymphoma - Kolbe, Clara Marie; Kauer, Joseph; Brinkmann, Berit J.; Dreger, Peter; Huber, Wolfgang; Müller-Tidow, Carsten; Dietrich, Sascha; Roider, Tobias (Journal for ImmunoTherapy of Cancer, 2025)
Bispecific antibodies (BsAb) have emerged as a leading treatment modality in patients suffering from B-cell non-Hodgkin’s lymphoma (B-NHL). However, treatment failure is common and may potentially be attributed to pre-existing or emerging T-cell exhaustion. CD39 catalyzes—together with CD73—the hydrolysis of immunogenic ATP into immunosuppressive adenosine and thus actively promotes an immunosuppressive micromilieu. Previously, we and others demonstrated that CD39+ T-cell subsets may have an adverse impact on the efficacy of T-cell-engaging immunotherapies. In this study, we applied an autologous ex vivo culture model of primary lymph node-derived T cells to investigate the potential of anti-CD39 or anti-CD73 blocking antibodies as T-cell enhancing combination partners of an anti-CD20 BsAb. Existing single-cell data of patient samples examined in this study were used to detect potential biomarkers predicting combination benefits. Combining anti-CD20 BsAb with anti-CD39 or anti-CD73 blocking antibodies induced synergistic effects on tumor cell killing, T-cell expansion and secretion of cytokines, including granzyme B, perforin, interleukin-10, interferon-γ, and tumor necrosis factor-α. We discovered that blockade of the CD39/CD73 pathway was particularly effective in patients with a high proportion of Programmed cell death protein 1 (PD-1)+ T-cell immunoglobulin and mucin-domain containing-3 (TIM3)+ exhausted T cells. Also, expression of CD39 in effector memory T cells indicated superior treatment benefit ex vivo. In summary, our study holds significant relevance as it introduces the combination of bispecific and anti-CD39 or anti-CD73 antibodies as a synergistic treatment approach in B-NHL, while also suggesting potential indicators to identify patients that might benefit from this treatment.